Pengaruh Kecanggihan Teknologi Informasi, Partisipasi Manajemen, Pengetahuan Manajer Akuntansi terhadap Efektivitas Sistem Informasi Akuntansi - Sasongko, Dian Arum (STIE Widya Manggala, 2020)
Managers need relevant, accurate, and reliable information just in time in order to make appropriate decisions. By accounting information system, the effectiveness can be achieved. The purpose of this study was to analyze the influence of information technology sophistication, management participation, accounting manager knowledge on accounting information system effectiveness of three stars and four stars hotels in Semarang. The samples were 80 accounting managers with the sampling techniques of purposive sampling. The analysis instrument of this study was multiple linear regression analysis. The result showed that information technology sophistication and management participation did not affect accounting information system effectiveness while accounting manager knowledge had a positive and significant effect on accounting information system effectiveness.